Employees’ Perception of Internal Audit Role in Promoting Accountability among Public Universities in Uganda: Evidence from Mbarara University of Science and Technology - Tumuhimbise, Manasseh; Kamugisha, Peter (International Journal of Sciences: Basic and Applied Research, 2018)
The paper examines how employees perceive the internal audit role in promoting accountability in Public Universities of Uganda. Assessment of internal audit focused on internal controls, procedures and practices. On the other hand, assessment of accountability in the study focused on transparency and compliancy. The Agency theory informed the study. A cross sectional survey in a case study design was adopted. Accordingly, Mbarara University of Science and Technology (MUST) was the case study. MUST, established by the Act of Parliament in 1993, and was purposively selected out of six (6) Public universities in Uganda. The six universities include Makerere, MUST, Kyambogo, Gulu, Busitema, and Muni (NCHE, 2015). Out of 196 respondents, data was collected by administering 182 questionnaires. Thus the study attained a response rate of 84.3%. The level of validity and reliability of the research instruments was at 0.951. Based on the perception responses, the study reveals presence of weak internal audit. Correspondingly, accountability was perceived weak too. Regression results confirm that internal audit as a predictor variable positively influences change in accountability (R2 = .347; p < 0.05). Therefore, this paper confirms that there is a weak perceived role of internal audit in promoting accountability at MUST. The paper concludes that Public Universities need to continuously improve and strengthen the internal audit function in order to promote accountability. Changes in internal control processes, procedures and practice yields proportionate positive change in accountability.The study recommends MUST executive to initiate measures to strengthen the internal audit function. In particular, the study recommends review of university internal controls. The university should also consider ‘individualizing and socializing’ internal audit procedures and practices by inspiring two-way communication among university staff
Keywords: Internal audit; Accountability; Public universities